Alternative dispute resolution mechanisms in Colombia and Rusia: conciliation and mediation (2021)
In this article, the authors compare alternative conflict resolution mechanisms in Colombia and Russia. In the former, conciliation is the most developed alternative dispute resolution mechanism, while in the latter, mediation is the most developed. In order to deepen this comparison, a qualitative research of interpretative nature has been developed with the support of bibliographic-documentary material. The main conclusion is that access to justice is a human right that has been positivized as a fundamental right in the constitutions of both Colombia and Russia. However, the Colombian Constitution allows individuals to exercise their jurisdictional functions on a temporary basis, unlike the Russian Constitution, which only authorizes judges from the Federation to exercise their jurisdictional functions. While conciliation in Colombia is developed and implemented through State-supervised Conciliation and Arbitration Centers, mediation in Russia is in its initial phase and has gradually gained acceptance in society. In both states, the implementation of alternative dispute resolution mechanisms has been driven by the need to decongest the courts and tribunals of ordinary justice. Therefore, it is useful to insist on the massive use of these instruments to make possible a justice that comes from the parties in conflict, that can repair the relations of the subjects in dispute and that tends towards the construction of more peaceful societies.